Mapeamento e validação de loci de caracteres quantitativos (QTL) para resistência a Cercospora zeae-maydis em milho tropical (Zea mays L.) - Pozar, Gilberto (2007)
Resistance to infection by Cercospora zeae-maydis (Cz) ranks among the most important objectives of breeding programs in Brazil. The objectives of this research were to map and characterize Quantitative Trait Loci (QTL) related to resistance to Cz, to validate the estimates of their effects on disease severity using Near- Isogenic Lines (NILs), and to estimate their effects on three major agronomic traits using their respective Near Isogenic Hybrids (NIHs) obtained by crossing the NILs with an inbred of complementary heterotic pool. Four QTL with LOD values > 2.5 were mapped using the Multiple Interval Mapping approach. Three of them were evaluated in this study. NILs genotype included the two QTL allele located in chromosome 1 in repulsion phase, Q1 in bin 1.05 and Q2 in bin 1.07, and one in chromosome 3, Q3 in bin 3.07. NIL evaluation showed that individually, the three QTL significantly reduced the severity of Cz. An unfavorable epistatic interaction for the reaction to Cz was detected between Q1 and Q2, in which one QTL allele effectively nullified the effect of the other. Alternatively, the interaction between Q2 and Q3 was positive, promoting the reduction of the severity to a greater extent than the sum of their individual effects. NIH evaluation revealed significant individual effects for Q1 and Q3 on Cz severity, for Q2 on stalk lodging and grain yield, and for Q3 on grain moisture and stalk lodging. Significant epistatic interactions were also detected between Q1 and Q2 for grain moisture and between Q1 and Q3 for stalk lodging. The combination of QTL impacts the effectiveness of marker-assisted selection procedures in commercial product development programs.